Virus clearance validation across continuous capture chromatography. Issue 9 (27th May 2019) - Angelo, James; Chollangi, Srinivas; Müller‐Späth, Thomas; Jusyte, Simona; Xu, Xuankuo; Ghose, Sanchayita; Li, Zhengjian
Abstract: Multicolumn capture chromatography is gaining increased attention lately due to the significant economic and process advantages it offers compared with traditional batch mode chromatography. However, for wide adoption of this technology in clinical and commercial space, it requires scalable models for executing viral validation studies. In this study, viral validation studies were conducted under cGLP guidelines to assess retro‐ (X‐MuLV) and parvo‐virus (MVM) clearance across twin‐column continuous capture chromatography (CaptureSMB). A surrogate model was also developed using standard batch mode chromatography based on flow path modifications to mimic the loading strategy used in CaptureSMB. The results show that a steady state was achieved by the second cycle for both antibody binding and virus clearance and that the surrogate model using batch mode chromatography equipment provided impurity clearance that was comparable to that obtained during cyclical operation of CaptureSMB. Further, the log reduction values (LRVs) achieved during CaptureSMB were also comparable to the LRVs obtained using standard batch capture chromatography. This was expected since the mode of virus separation during protein A chromatography is primarily based on removal during the flow through and wash steps. Finally, this study also presents assessments on the resin cleaning strategy during continuous chromatography and how the duration of clean‐in‐place solution exposure impacts virus carryover. Abstract : Multicolumn capture chromatography is gaining increased attention lately due to the significant economic and process advantages it offers compared with traditional batch mode chromatography. However, for wide adoption of this technology in clinical and commercial space, it requires scalable models for executing viral validation studies. In this study, viral validation studies were conducted under cGLP guidelines to assess retro‐ (X‐MuLV) and parvo‐virus (MVM) clearance across twin‐column continuous capture chromatography (CaptureSMB).